Problematika Residivis Kekerasan Seksual Terhadap Anak Setelah Eksekusi Pidana Tambahan Kebiri Kimia - Ghatfhan Hanif; Rosalia Dika Agustanti (Universitas Medan Area, 2022)
This paper aims to analyze the construction of criminal law that is relevant to human rights (HAM) and establish progressive legal reinforcement in responding to current legal issues so that the problems of this paper can be focused on elements of recidivism, chemical castration, and progressive law. The research method uses normative research methods with a literature study approach and is then analyzed qualitatively. The results of the study conclude that progressive legal dialectic orients towards human welfare and happiness. Criminal law regulates violations and crimes that exist in acts of human behavior, indeed the concept of law in Indonesia adheres to civil law, which means that the substance and explanation are codified and recorded, so in the context of crimes of sexual violence that have been regulated in the Criminal Code (KUHP) , laws on child protection, and government regulations on chemical castration that are textually formulated (books). The legal principle views legal certainty, justice and usefulness, but in the context of the use of chemical castration on recidivists it seems paradoxical, on the one hand it wants to deter, on the other hand it wants to treat or recover.